The impact of demand management strategies on parents’ decision-making for out-of-hours primary care: findings from a survey in The Netherlands - Giesen, Marie-Jeanne; Wensing, Michel (BMJ open, 2017)
Objective To explore the potential impact of demand management strategies on patient decision-making in medically non-urgent and urgent scenarios during out-of-hours for children between the ages of 0 and 4 years. Design and methods We conducted a cross-sectional survey with paper-based case scenarios. A survey was sent to all 797 parents of children aged between 0 and 4 years from four Dutch general practitioner (GP) practices. Four demand management strategies (copayment, online advice, overview medical cost and GP appointment next morning) were incorporated in two medically non-urgent and two urgent case scenarios. Combining the case scenarios with the demand management strategies resulted in 16 cases (four scenarios each with four demand management strategies). Each parent randomly received a questionnaire with three different case scenarios with three different demand strategies and a baseline case scenario without a demand management strategy. Results The response rate was 47.4%. The strategy online advice led to more medically appropriate decision-making for both non-urgent case scenarios (OR 0.26; 95% CI 0.11 to 0.58) and urgent case scenarios (OR 0.16; 95% CI 0.08 to 0.32). Overview of medical cost (OR 0.59; 95% CI 0.38 to 0.92) and a GP appointment planned the next morning (OR 0.57; 95% CI 0.34 to 0.97) had some influence on patient decisions for urgent cases, but not for non-urgent cases. Copayment had no influence on patient decisions. Conclusion Online advice has the highest potential to reduce medically unnecessary use. Furthermore it enhanced safety of parents' decisions on seeking help for their young children during out-of-hours primary care. Valid online information on health symptoms for patients should be promoted.